Antibacterial therapy in general medical wards. Issue 620 (June 1977) - Lawson, D. H.; MacDonald, S.
Abstract : Information from a comprehensive drug surveillance programme is analysed to provide details of antibacterial drug use in medical wards. Some 28% of patients received antibacterial therapy, usually for the treatment of respiratory or urinary tract infections. The agents most frequently prescribed were ampicillin, co-trimoxazole and tetracyclines. Overall, 11% of recipients experienced one or more adverse effect of therapy. No significant bacterial growth was obtained from some 40% of specimens of sputum sent from patients. A plea is made for more rational use both of sputum culture in the investigation of patients with respiratory infection and of antibiotics in their treatment.